The Influence of Minimum Wage Policies on Work Engagement within the Manufacturing Sector in Kinta, Perak: The Mediating Role of Financial Security - Dars, Grace Anthony; Dars, Alexandar Anthony; Silvarajee, Asvini; Mohamad, Shafi; Nor , Sarina Mohamad; Kanapathipillai , Kumaran (International Review of Management and Marketing, 2025)
In this study, minimum wage policy has been investigated on its impact on work engagement of manufacturing sector employees in Kinta, Perak, Malaysia using financial security as a mediating variable. Even though Malaysia has legislated minimum wage to increase employee welfare, there is little research on its psychological and behavioural impact. The study explores the effects of three dimensions of minimum wage policy being wage level adequacy, wage implementation consistency, and wage policy transparency on work engagement independently as well as indirectly through financial security with the Conservation of Resources (COR) Theory. The research employed a quantitative research design based on employees aged 18-60 in years, and a total of 422 valid responses were obtained by stratified random sampling and were analyzed in SPSS and PROCESS Macro Model 4. Results show that financial security partially mediates all three dimensions to influence work engagement significantly and positively. The strongest direct effect among the predictors, and the most indirect influence from wage adequacy, was found in wage policy transparency, and less indirect influence from financial security. The policy implications are important for policymakers, HR practitioners, and industry leaders to consider raising wages that would improve financial stability and workplace engagement.